2012
DOI: 10.1007/s10459-012-9377-9
|View full text |Cite
|
Sign up to set email alerts
|

Feedback sandwiches affect perceptions but not performance

Abstract: The feedback sandwich technique-make positive comments; provide critique; end with positive comments-is commonly recommended to feedback givers despite scant evidence of its efficacy. These two studies (N = 20; N = 350) of written peer feedback with third-year medical students on clinical patient note-writing assignments indicate that students think feedback sandwiches positively impact subsequent performance when there is no evidence that they do. The effort necessary to produce feedback sandwiches and studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 12 publications
0
54
0
1
Order By: Relevance
“…Ende defined feedback in medical education as Binformation describing students or house officers' performance in a given activity that is intended to guide their future performance in the same activity.^1 The Bfeedback sandwich^model, which recommends starting and ending with positive feedback, interposed by negative feedback, 21 has not been shown to improve learner performance. 22 The Pendleton model features four key steps: learner selfassessment of strengths, teacher agreement/disagreement, learner assessment of deficiencies, and teacher agreement/ disagreement. 23 However, most older definitions and models have not adequately showcased learner engagement in the conversation or their role in creating a road map for performance improvement.…”
Section: Traditional Definitions and Modelsmentioning
confidence: 99%
“…Ende defined feedback in medical education as Binformation describing students or house officers' performance in a given activity that is intended to guide their future performance in the same activity.^1 The Bfeedback sandwich^model, which recommends starting and ending with positive feedback, interposed by negative feedback, 21 has not been shown to improve learner performance. 22 The Pendleton model features four key steps: learner selfassessment of strengths, teacher agreement/disagreement, learner assessment of deficiencies, and teacher agreement/ disagreement. 23 However, most older definitions and models have not adequately showcased learner engagement in the conversation or their role in creating a road map for performance improvement.…”
Section: Traditional Definitions and Modelsmentioning
confidence: 99%
“…Tem a intenção de suavizar a mensagem que pode ser vista como negativa, porém, alguns autores relatam o risco de os alunos não darem atenção ao feedback corretivo e alcançar menor resultado no desempenho 22 . Outra estratégia recomendada é iniciar solicitando que o aluno faça sua autoavaliação.…”
Section: -53unclassified
“…However, in assessing the effectiveness of the feedback sandwich (positive feedback, followed by constructive feedback, and finally providing additional positive feedback) among medical students, Parkes, Abercrombie, and McCarty (2013) found that the use of substantial positive feedback may hinder students' ability to critically evaluate their performance by sending mixed messages regarding performance and minimizing the significance of the constructive feedback.…”
Section: Feedback Types and Preferencesmentioning
confidence: 99%
“…Thus, it appears that the integration of positive feedback may assist students with being more open to the feedback process, including the use of constructive feedback (Coleman, Kivlighan, & Roehlke, 2009) by helping them increase their self-efficacy as a counselor and decrease their anxiety (Daniels & Larson, 2001); however, this may not improve performance (Parkes et al, 2013). Nevertheless, the best outcome may result from balancing positive and constructive feedback in order to promote satisfaction while also encouraging change (Boehler et al, 2006).…”
Section: Feedback Types and Preferencesmentioning
confidence: 99%